Coverage of work related fatalities in Australia by compensation and occupational health and safety agencies. Issue 3 (1st March 2003) - Driscoll, T; Mitchell, R; Mandryk, J; Healey, S; Hendrie, L; Hull, B
Abstract : Aims: To determine the levels of coverage of work related traumatic deaths by official occupational health and safety (OHS) and compensation agencies in Australia, to allow better understanding and interpretation of officially available statistics. Methods: The analysis was part of a much larger study of all work related fatalities that occurred in Australia during the four year period 1989 to 1992 inclusive and which was based on information from coroners' files. For the current study, State, Territory, and Commonwealth OHS and compensation agencies were asked to supply unit record information for all deaths identified by the jurisdictions as being due to non-suicide traumatic causes and which were identified by them as being work related, using whatever definitions the agencies were using at the relevant time. This information was matched to cases identified during the main study. Results: The percentage of working deaths not covered by any agency was 34%. Only 35% of working deaths were covered by an OHS agency, while 57% were covered by a compensation agency. The OHS agencies had minimal coverage of work related deaths that occurred on the road (to workers (8%) or commuters (3%)), whereas the compensation system covered these deaths better than those of workers in incidents that occurred in a workplace (65% versus 53%). There was virtually no coverage of bystanders (less than 8%) by either type of agency. There was marked variation in the level of coverage depending on the industry, occupation, and employment status of the workers, and the type of injury event involved in the incident. Conclusions: When using data from official sources, the significant limitations in coverage identified in this paper need to be taken into account. Future surveillance, arising from a computerised National Coroners Information System, should result in improved coverage of work related traumatic deaths in Australia.